Functional and Oncologic Outcomes of Octogenarians Undergoing Transoral Laser Microsurgery for Laryngeal Cancer. Issue 3 (September 2021) - Lee, Changseok; Forner, David; Noel, Christopher W.; Taylor, Victoria; MacKay, Colin; Rigby, Matthew H.; Corsten, Martin; Trites, Jonathan R.; Taylor, S. Mark
Objective: To evaluate the oncologic and functional outcomes of transoral laser microsurgery (TLM) for glottic cancers in patients ≥80 years. Study Design: Prospectively collected case series. Setting: QEII Health Sciences Centre, Halifax, Canada. Methods: This case series used a prospectively collected glottic cancer database to examine consecutive elderly patients (≥80 years old) undergoing TLM. Kaplan-Meier analysis was used to evaluate rates of disease-free, disease-specific, and overall survival as the primary end points of oncologic control. Secondary functional outcomes included voice function, length of hospital stay, and time to readmission. Results: From 2005 to 2017, 17 octogenarian patients underwent TLM for glottic cancer. Median follow-up was 4.19 years (interquartile range, 0.71-6.95). Kaplan-Meier estimates of 5-year survival were 78.4% (disease free), 92.9% (disease specific), and 81.9% (overall). The median length of hospital stay was 1 day (range, 0-8). There was only 1 readmission within 30 days of surgery. No patients in this study developed significant surgical or postoperative complications requiring unplanned readmissions. Patient-perceived voice function improved to normal after treatment in 62.5% of patients. Conclusion: The results of this study suggest that TLM is a safe and effective treatment modality for glottic cancer in patients aged ≥80 years, providing good oncologic control and satisfactory functional outcomes.